The Influence of The Working Discipline, Organizational Commitment and Reply Jasa Against Employee Performance Bappeda East Halmahera Regency - Abdul Rahman, Hasna; Lewangka, Osman; Abduh, Thamrin (Indonesian Journal of Business and Management, 2018)
This study aims to test and analyze the work discipline of positive and significant effect on performance clerk Bappeda East halmahera Regency, the moderating influence of Retribution against the work performance of the employee discipline Bappeda East halmahera Regency, organizational commitment and significant positive effect on performance clerk Bappeda East halmahera Regency, and retribution to moderate the influence of organizational commitment on performance clerk Bappeda kabupaten East Halmahera. Methods of analysis used in this study was multiple linear regression that analysts used to analyze whether the variable eksogenus (a work discipline, organizational commitment, and retribution) affect variable endogenus (performance employees). The research results showed that the variables work discipline, organizational commitment, and retribution is positive and significant effect on performance in the next variable employee discipline of work and organisational commitment is also positive and significant effect against retribution on halmahera Regency or halmahera bappeda timurdari test results have significance > t-table, or 5,050 > 1,679, then disciplined to work influential and significantly to the performance of the employees. t-female > t-table, or 5,769 > 1,679, then the most influential and significant organizational commitment against the performance of employees.